Enhancing H2O2 and glucose double detection by surface microstructure regulation of Brussels sprout-like Ni–Co(OH)2/rGO/carbon cloth composites. Issue 18 (20th April 2022) - Zhang, Xinmeng; Mao, Zixuan; Ge, Wanyin; Zhu, Jiajing; Zhao, Yuanxiao
Abstract : Carbon cloth and rGO enhanced the performance of Brussels sprout-like Ni–Co(OH)2 for the detection of H2 O2 and glucose. Abstract : Surface microstructure regulation is an effective way to enhance the performance of sensing materials. Here, a hierarchical and flexible Brussels sprout-like Ni–Co(OH)2 /rGO/carbon cloth (CC) composite was constructed by optimizing the morphology of Ni–Co(OH)2 microspheres and the addition amount of rGO. This sensor shows excellent reproducibility, high selectivity, and good stability. It shows a high sensitivity of 3.7391 mA mM −1 cm −2 in the 0.0388–124.0436 mM line detection range for H2 O2 and 1.8457 mA mM −1 cm −2 in the 0.0300–2.0000 mM line detection range for glucose. The low limits of detection for H2 O2 and glucose are 2.316 nM and 0.115 μM, respectively. The excellent electrochemical performance of the Ni–Co(OH)2 /rGO/CC composite is attributed to its unique Brussels sprout-like microstructure. By studying the electrical conductivity, electrochemical active surface area, and hydrophilic–hydrophobic surfaces of the Ni–Co(OH)2 /rGO/CC composite, the structure–performance relationship between the microstructure and sensing performance of the composite was further clarified. Moreover, the mechanism of CC, rGO, and the Ni–Co(OH)2 ternary composite in the sensing process is proposed. This study provides a new strategy for the construction of flexible wearable electrodes with high sensitivity.